An Overview of Computational Models for Industrial Internet of Things to Enhance Usability - Zhen Ying; Iftikhar Ahmad; Saima Mateen; Asad Zia; Ambreen; Shah Nazir; Neelam Mukhtar (Complexity)
In the last decade, the Internet of Things (IoT) has grown to connect a large number of smart entities, devices, and components. These connected entities provide a wide range of services to improve the current society of end customers. The Industrial Internet of Things (IIoTs) are revolutionary systems that have linked manufacturing processes with Internet access in order to preciously increase quality of services. These systems have minimized the costs of production through collaboration with electronic objects, accumulating computing, advanced analytics, and smart perception techniques. A demanding analysis of the strengths and limitations of computational models of IIoT is an essential part of the industry and before deciding which approach to use and implement for enhancing usability. Therefore, the goal of this study is to provide feedback and information to the research community and identify patterns in recommendations for future research in the context of process, development, and monitoring of additional technologies of computational models for IIoT. This paper has presented a comprehensive summary of the existing literature on IIoT for providing details about modern industrial revolutions in the context of IIoT. Associated materials were searched and filtered for identification of relevant materials to the proposed study. These materials have been collectively studied with in-depth analysis and then summarized to condense the information of computation models for the readers as well as entrepreneurs. The study will facilitate research community and practitioners to develop novel techniques, algorithms, and tools to automate and facilitate IIoT. This will develop the field of IIoT and will enhance its usability.